2021
DOI: 10.1002/ldr.4081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different tillage management on rhizosphere soil nitrogen mineralization and its extracellular enzyme activity in a double‐cropping rice paddy field of southern China

Abstract: Soil extracellular enzyme activity plays an important role in regulating the process of nitrogen (N) mineralization in the paddy field. However, there is still limited information about how rhizosphere N mineralization and its extracellular enzyme activities respond to different tillage treatments in a double-cropping rice paddy fields of southern China.Therefore, the effects of 6-year (short-term) tillage management on rhizosphere soil acid hydrolysable N and its fractions, N mineralization, and its extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…BG regulates the release of soil glucose, and UR regulates the decomposition of urea, both of which are important enzymes in soil C and N cycles [47,48]. We observed that tillage increased the activity of BG and UR, which was consistent with previous conclusions [49]. In this study, tillage increased SOC content, thus stimulating the synthesis of BG and UR [50].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BG regulates the release of soil glucose, and UR regulates the decomposition of urea, both of which are important enzymes in soil C and N cycles [47,48]. We observed that tillage increased the activity of BG and UR, which was consistent with previous conclusions [49]. In this study, tillage increased SOC content, thus stimulating the synthesis of BG and UR [50].…”
Section: Discussionsupporting
confidence: 92%
“…Returning straw provides more substrates and energy sources for enzyme synthesis [53]. PT combined with returning straw had higher BG and UR at the tillering stage of rice in the main season, which may be because tillage fully mixed the straw and soil, which promoted the decomposition of straw and the synthesis of enzymes [49].…”
Section: Discussionmentioning
confidence: 99%
“…, soil N, SOM contents) were enhanced under tillage and crop straw input conditions [ 19 ], which suggests that SOM provides more soil nutrients for rice. Furthermore, our results proved that soil N mineralization rates with RT and CT treatments were higher than that of NT treatment, indicating that soil chemical properties (soil N and SOM contents) were deficient with no-tillage and crop straw input treatments [ 4 , 20 ]. Meanwhile, our results proved that soil N transformation rates in rice field with CT treatments were higher than that of RT treatment, which suggested the existence of higher levels of soil soluble N, and a larger soil active N pool in rice fields under conventional tillage condition, in addition to improved quality of SOM with crop straw input practice.…”
Section: Discussionmentioning
confidence: 95%
“…The information regarding method and number of rhizosphere soil samples followed that reported by Tang et al . (2021) [ 4 ]. All soil samples were divided into two parts after removing the foreign matter ( e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation